1990
DOI: 10.1007/bf02247879
|View full text |Cite
|
Sign up to set email alerts
|

Computational aspects of a branch and bound algorithm for quadratic zero-one programming

Abstract: --ZasammenfassungComputational Aspects of a Branch and Bound Algorithm for Quadratic Zero-One Programming. In this paper we describe computational experience in solving unconstrained quadratic zero-one problems using a branch and bound algorithm. The algorithm incorporates dynamic preprocessing techniques for forcing variables and heuristics to obtain good starting points. Computational results and comparisons with previous studies on several hundred test problems with dimensions up to 200 demonstrate the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
130
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(135 citation statements)
references
References 16 publications
1
130
0
4
Order By: Relevance
“…Pardalos and Rodgers [37], [38] solve (QP) by Branch-and-Bound using a preprocessing phase where they try to fix some of the variables. The test on fixing the variables is based on the gradient of (1), which reads 2Qy + c, and exploits the fact that if y * is the global solution of (QP), then y * is also optimal for the linear program min{(2Qy * + c) T y : y ∈ {0, 1} n }.…”
Section: Further Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pardalos and Rodgers [37], [38] solve (QP) by Branch-and-Bound using a preprocessing phase where they try to fix some of the variables. The test on fixing the variables is based on the gradient of (1), which reads 2Qy + c, and exploits the fact that if y * is the global solution of (QP), then y * is also optimal for the linear program min{(2Qy * + c) T y : y ∈ {0, 1} n }.…”
Section: Further Approachesmentioning
confidence: 99%
“…Pardalos and Rodgers ( [37]) have proposed a test problem generator for Unconstrained Quadratic Binary Programming. Their procedure generates a symmetric integer matrix Q to define the objective function for (QP), with the linear term c represented by the main diagonal of Q, and has several parameters to control the characteristics of the problem, namely:…”
Section: Instances Of (Qp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are several exact methods using branch and bound or branch and cut (see, e.g., [8,22,23,42]), but the high computational complexity of UBQP and the breadth of applications it embraces has led to the finding that, apart from isolated cases, problems of sizes larger than n = 100 cannot be solved by these exact methods in a reasonable time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many combinatorial optimization problems pertaining to graphs such as determining maximum cliques, maximum cuts, maximum vertex packing, minimum coverings, maximum independent sets, maximum independent weighted sets are known to be capable of being formulated by the UBQP problem as documented in papers of Pardalos and Rodgers (1990), Pardalos and Xue (1994). A review of additional applications and formulations can be found in Kochenberger et al (2004Kochenberger et al ( , 2005, Alidaee et al (2008), Lewis et al (2008).…”
Section: Introductionmentioning
confidence: 99%